Conceptualizing Value Creation in the Platform Era. (November 2022) - Wichmann, Julian R.K.; Reinartz, Werner; Venkatesan, Rajkumar
Platforms have entered many industries and increasingly dominate markets. As such, they increasingly displace the traditional linear pipeline model of value creation with a web of value-creating interactions among three key players: the platform provider, platform consumers and platform suppliers. Existing conceptualizations of consumer value, however, are still based in the linear pipeline world which raises the need to update these frameworks to the platform era. In this article, we make first important strides towards an overarching platform-based valuation framework which can be applied to any type of platform. We build uponKumar et al. (2010) by applying and extending the concept of customer engagement value to the platform context. In doing so, we delineate a variety of value components that (a) originate from a platform's consumers as well as suppliers, (b) generate monetary and non-monetary value for the platform provider, and (c) generate direct and indirect value for the platform provider. Together, these value components holistically capture platform participants' value creation and assist managers in evaluating the health and sustainability of their platforms.